Insertion/Deletion Within the KDM6A Gene Is Significantly Associated With Litter Size in Goat - Cui, Yang; Yan, Hailong; Wang, Ke; Xu, Han; Zhang, Xuelian; Zhu, Haijing; Liu, Jinwang; Qu, Lei; Lan, Xianyong; Pan, Chuanying (Frontiers in Genetics, 2018)
A previous whole-genome association analysis identified lysine demethylase 6A (KDM6A), which encodes a type of histone demethylase, as a candidate gene associated to goat fecundity. KDM6A gene knockout mouse disrupts gametophyte development, suggesting that it has a critical role in reproduction. In this study, goat KDM6A mRNA expression profiles were determined, insertion/deletion (indel) variants in the gene identified, indel variants effect on KDM6A gene expression assessed, and their association with first-born litter size analyzed in 2326 healthy female Shaanbei white cashmere goats. KDM6A mRNA was expressed in all tissues tested (heart, liver, spleen, lung, kidney, muscle, brain, skin and testis); the expression levels in testes at different developmental stages (1-week-old (wk), 2 wk, 3 wk, 1-month-old (mo), 1.5 mo and 2mo) indicated a potential association with the mitosis-to-meiosis transition, implying that KDM6A may have an essential role in goat fertility. Meanwhile, two novel intronic indels of 16 bp and 5 bp were identified. Statistical analysis revealed that only the 16 bp indel was associated with first-born litter size (P < 0.01), and the average first-born litter size of individuals with an insertion/insertion genotype higher than that of those with the deletion/deletion genotype (P < 0.05). There was also a significant difference in genotype distributions of the 16 bp indel between mothers of single-lamb and multi-lamb litters in the studied goat population (P = 0.001). Consistently, the 16 bp indel also had a significant effect on KDM6A gene expression. Additionally, there was no significant linkage disequilibrium between these two indel loci, consistent with the association analysis results. Together, these findings suggest that the 16 bp indel in KDM6A may be useful for marker-assisted selection of goats.